1973
DOI: 10.1149/1.2403622
|View full text |Cite
|
Sign up to set email alerts
|

Change in pH near the Cathode During the Electrodeposition of a Bivalent Metal. Analysis

Abstract: An important factor in the cathodic electrodeposition of a base metal (M) is the increase in pH (“alkalization”) of the electrolyte near the cathode.Chemical equilibria and transport processes in the cathodic diffusion layer are analyzed by numerical integration of the transport equations. The analysis shows that alkalization is caused by the production of OH− at the cathode and is prevented when the hydroxyl ions so produced react to form a soluble species (e.g., MOH+ or H2O ).When complex ions are not forme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0
4

Year Published

1973
1973
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 7 publications
0
29
0
4
Order By: Relevance
“…111 Thus, to produce metallic films, buffers and complexing agents such as boric acid are commonly added to the electrolyte to mitigate the effects of pH changes. 2,1214 …”
Section: Introductionmentioning
confidence: 99%
“…111 Thus, to produce metallic films, buffers and complexing agents such as boric acid are commonly added to the electrolyte to mitigate the effects of pH changes. 2,1214 …”
Section: Introductionmentioning
confidence: 99%
“…Other roles ascribed for boric acid have been to act as a buffer [14,15], catalyst for metal deposition [16,17] and co-adsorbate on the cathode [18,19]. Zech and Landolt [19] reported that the presence of boric acid shifts the potential for proton reduction in the negative direction and lowers the pH rise at the cathode surface.…”
Section: Introductionmentioning
confidence: 99%
“…The changes of pH at the cathode during electroplating of transition metals and alloys have been studied by many investigators [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Kuhn and Chan [2] have presented a review of different techniques by which near-surface pH levels have been measured.…”
Section: Introductionmentioning
confidence: 99%
“…Harris [8] developed a mathematical model which predicted hydroxyl ion of OH" concentrations in the diffusion layer during the deposition of a bivalent metal. On the basis of a proposed model, he concluded that the degree of cathode alkalization depends on the rate of H^ consumption at the cathode, buffering reactions in the diffusion layer, and complexation reactions of the metallic ions with the anions present.…”
Section: Introductionmentioning
confidence: 99%